Cryonarratives for Warming Times: Icebergs as Planetary Travellers - Elizabeth Leane (2022)
In the Anthropocene, icebergs have moved from the periphery to the centre of global public consciousness, their ephemerality and mutability ominously signalling the mobile and impermanent nature of the polar regions. With ice sheets and ice shelves increasingly unstable as ocean temperatures rise, humans feel implicated for the first time in the creation of these objects. The calving of a huge tabular berg is now a political event, framed by media headlines worldwide not simply as a visual spectacle but also as a source of communal guilt, fear, anxiety and anger. Yet such icebergs can endure for decades beyond this sensationalised moment, wandering peripatetically through the oceans and interacting with human and nonhuman actors in diverse and unpredictable ways. This chapter proposes a new term, 'cryonarrative,' as a shorthand for the kinds of stories that humans are telling about ice in the contemporary period, and looks at the particular cryonarratives being applied to icebergs. Within media and tourist discourse, icebergs are often subject to reductive narratives that render them as symbols of human doom or aesthetic objects for human consumption. As a remedy to this anthropocentric approach, I argue for the advantages of characterising and narrating icebergs as travellers on a planetary scale.